Cytotoxicity and antimicrobial effects of citronella oil (Cymbopogon nardus) and commercial mouthwashes on S. aureus and C. albicans biofilms in prosthetic materials - Guandalini Cunha, Bruno [UNESP]; Duque, Cristiane [UNESP]; Sampaio Caiaffa, Karina [UNESP]; Massunari, Loiane [UNESP]; Araguê Catanoze, Isabela [UNESP]; dos Santos, Daniela Micheline [UNESP]; de Oliveira, Sandra Helena Penha [UNESP]; Guiotti, Aimée Maria [UNESP] (Elsevier, 2020)
Although the effectiveness of some mouthwashes has been proven, phytotherapy is still a field to be explored as an alternative to commercial products. Objective: To evaluate, in vitro, the cytotoxicity and efficacy of two solutions based on citronella oil (CN), on S. aureus and C. albicans biofilms (in formation–adhesion phase and 24 h-biofilm formation) on acrylic resin and nickel-chromium alloy samples (one trademark of each material), compared to two alcohol-free commercial mouthwashes. Material and Methods: Two solutions containing CN at concentrations of 5x and 10x the minimum bactericidal/fungicidal concentration (MBC/MFC) were prepared by microdilution. After contamination of the samples surfaces with these microorganisms, the mouthwashes (CN - 5x and 10x; CHX - 0,12% alcohol-free chlorhexidine and LT - alcohol-free essential oils) were evaluated. Mouthwash simulation was performed for 1 min at two moments, the first simulation after 4 h of microbial adhesion and 24 h-biofilm formation, and the second simulation, 6 h after the first simulation. For biofilm quantification, the number of cultured cells was evaluated by CFUs. The cytotoxicity assay was performed on HaCat epithelial cells and quantified by the MTT method. Results: Tested solutions completely inhibited the growth of both microorganisms in the adhesion phase. All solutions showed inhibitory activity against 24 h-biofilm formation. However, CN led to greater microbial reduction, regardless of the surface of the sample. All solutions demonstrated a toxic effect. However, after serial dilution, CN presented the lowest cytotoxic effect. Conclusion: Citronella had a lower cytotoxic effect and a higher action compared to commercial solutions.
Keywords: Acrylic resins; Biofilms; Candida albicans; Cymbopogon; Staphylococcus aureus